The Impacts of the Analysis, Debate, and Finding Models on Learning Natural Sciences - Apdoludin Apdoludin; Megawati Megawati; Randi Eka Putra; Dodi Harianto; Wiwik Pudjaningsih; Elfa Eriyani (Qubahan Academic Journal)
Problem solving of low critical thinking skills, difficulty in practicing science skills, analyzing students' concepts in depth and low learning outcomes are serious problems that must be solved. This experimental study aims to compare critical thinking skills, science skills, students' analytical skills and learning outcomes between the two groups, namely the pre-test and post-test control groups. This study involved 26 students of grade 5 SDN 196/II Taman Agung, Bathin III District, Bungo Regency, totaling 26 students. The results showed that students had critical thinking skills, practicing science skills, and analyzing students' concepts in depth who believed that knowledge related to the material must be justified in various ways that showed broader and positive epistemics as evidenced by a significant increase in the science learning outcomes of grade 5 students of SDN 196/II Taman Agung, Bathin III District, Bungo Regency with a learning model of debate, analysis, and findings through experimental methods.